Physical Contact with Material Objects – Sensory Marketing Perspective - Arnold PABIAN; Aleksander PABIAN (Communications of International Proceedings, 2020)
Tactile marketing is a relatively poorly explored area of sensory marketing. The research that has been conducted so far in this area concentrates primarily on utilising the touch sense while selling material products. Researchers have predominantly focused on hands, which are the receivers of sensor stimuli. The authors of the present paper consider tactile stimuli that come from a number of various sources and appeal to several, diverse parts of human body. The objective of the paper is to present, based on own research, tactile preferences of consumers aged 15-23 in the aspect of their presence inside various types of commercial and service facilities. The research was conducted on the sample of 430 persons. Majority of young consumers prefer sufficient free space where they can move freely. Their  remaining tactile preferences are as follows: walls covered with natural wood or paints put on plaster; floors made of natural wood, ceramic tiles, and also covered with carpets; soft floor coverings in the form of carpets, carpeting, rugs; bed places neither excessively firm nor excessively soft; seats covered with fabric or natural leather upholstery – soft or neither soft nor firm; objects that can be touched – rounded with soft surface.
Keywords: Tactile marketing; tactile preferences; young consumers.